A system approach in energy evaluation of different renewable energies sources integration in ammonia production plants. (December 2016) - Frattini, D.; Cinti, G.; Bidini, G.; Desideri, U.; Cioffi, R.; Jannelli, E.
Abstract: A sustainable pathway for ammonia synthesis by means of the Haber-Bosch process should reduce or zero out the use of fossil fuels, taking advantage of renewable sources. Using renewable energy systems, hydrogen can be obtained from biomass gasification, biogas reforming or electrolysis of water with electricity generated by solar or wind energy. The scale-up of the concept is not an easy issue. From a theoretical point of view there is no limit to multiply single units but on a practical way, chemical companies are hardly reaching the size of 100 kW, due to energy, economic and sustainability problems. Hydrogen, from high-temperature water electrolysis, from biomass gasification and from biogas reforming, has been considered as the most promising solutions for ammonia production plants, based on the Haber-Bosch process. In this study the impact of three different strategies, for renewables integration and scale-up sustainability in the ammonia synthesis process, was investigated using thermochemical simulations. The study is finalized to compare the energy efficiency and sustainability of those three strategies. For a complete evaluation of the benefits of the overall system, the balance of plant, the use of additional units and the equivalent greenhouse gas emissions have been considered. Highlights: Haber-Bosch process fed with renewable sources for green NH3 is modelled in Aspen. Efficiency, energy flows and greenhouse gas emissions are calculated and compared. Use of renewables is mainly limited by the content of inert gases in feed stream. Total energy consumptions are similar to the reference case fed with methane.